Analisis Kebutuhan dan Literasi Kesehatan Siswa SMP dalam Upaya Pencegahan Gaya Hidup Sedentari - Ngurah Mahendra Dinatha (Lontara Journal of Health Science and Technology, 2026)
The shift toward a modern lifestyle increasingly dependent on technology has created new challenges in the field of health, particularly among adolescents. Junior high school students are a vulnerable group to sedentary lifestyles, characterized by limited physical activity due to passive habits such as using gadgets and watching television. This condition affects both the physical and mental health of students, highlighting the need for effective health education strategies to foster active living habits from an early age. This study aims to analyze students’ health literacy levels and their needs in preventing sedentary lifestyles. A descriptive quantitative approach was employed at SMPN 1 Bajawa, Ngada Regency, East Nusa Tenggara. The research sample consisted of 152 students selected through proportional random sampling. Data were collected using a closed-ended Likert-scale questionnaire (1–5) covering demographic information, health literacy, and the needs and barriers to adopting an active lifestyle. Data analysis was conducted descriptively and inferentially using SPSS version 26, applying the Kolmogorov–Smirnov normality test and Pearson Product Moment correlation test. The results showed that students’ health literacy levels were categorized as moderate to high (mean = 78.45), while the need for sedentary lifestyle prevention was at a moderate level (mean = 74.63). There was a strong and significant positive correlation (r = 0.648; p < 0.05) between health literacy and the need for sedentary lifestyle prevention. It was concluded that improving health literacy plays a crucial role in fostering students’ awareness of the importance of an active lifestyle. Therefore, participatory and contextual educational programs in schools are essential to promote sustainable healthy behaviors.